2019
DOI: 10.1101/gad.325662.119
|View full text |Cite
|
Sign up to set email alerts
|

Daedalus and Gasz recruit Armitage to mitochondria, bringing piRNA precursors to the biogenesis machinery

Abstract: The Piwi-interacting RNA (piRNA) pathway is a small RNA-based immune system that silences mobile genetic elements in animal germlines. piRNA biogenesis requires a specialized machinery that converts long singlestranded precursors into small RNAs of ∼25-nucleotides in length. This process involves factors that operate in two different subcellular compartments: the nuage/Yb body and mitochondria. How these two sites communicate to achieve accurate substrate selection and efficient processing remains unclear. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 51 publications
9
49
1
Order By: Relevance
“…The probe used was for idefix-piRNA arising from the flam locus. These findings corroborated the notion that Gasz acts in conjunction with Daed as the platform for Zuc-dependent piRNA maturation from piRNA precursors [20]. Without Gasz, mature idefix-piRNA almost disappeared but the piRNA precursors strongly accumulated, as was the case upon Zuc depletion (Fig 1A).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The probe used was for idefix-piRNA arising from the flam locus. These findings corroborated the notion that Gasz acts in conjunction with Daed as the platform for Zuc-dependent piRNA maturation from piRNA precursors [20]. Without Gasz, mature idefix-piRNA almost disappeared but the piRNA precursors strongly accumulated, as was the case upon Zuc depletion (Fig 1A).…”
Section: Resultssupporting
confidence: 86%
“…These results suggest that, without Gasz, regardless of the presence or absence of Zuc, Armi no longer remains on the mitochondrial surface and so returns to Yb bodies while leaving Piwi in the cytosol. Previous studies showed that Gasz loss perturbs mitochondrial morphology in OSCs [17,20], which was also observed but to a lesser extent in this study ( Fig EV1E). Previous studies showed that Gasz loss perturbs mitochondrial morphology in OSCs [17,20], which was also observed but to a lesser extent in this study ( Fig EV1E).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Analysis of ovarian transcription profiles suggests that regions facilitating convergent transcription favor the formation of transgenic piRNA clusters.Cells 2020, 9, 922 2 of 19 piRNA clusters [3][4][5]. In germ cells, in contrast to protein-coding mRNAs, piRNA precursors are delivered to the piRNA processing machinery localized in the specialized cytoplasmic structure, "nuage", and on the outer mitochondrial membrane [6][7][8][9]. piRNA-mediated silencing is a potent mechanism of expression control realized through transcriptional [10,11] and co-transcriptional [12] repression of target loci.…”
mentioning
confidence: 99%
“…Female sterile (1) Yb (Yb), Armitage (Armi), Sister of Yb (SoYb), Vreteno (Vret), and Shutdown (Shu) are detected at Yb bodies, while Zucchini (Zuc), Gasz, Minotaur (Mino), and Daedalus (Daed) are detected on mitochondria (for details, see Sections 4 and 5) [60][61][62][63][64][65][66][67][68]. Armi, Vret, and Zuc are also expressed in germ cells [48,63,[67][68][69][70][71][72][73][74][75][76]. Germ-specific factors include Brother of Yb (BoYb), Spindle-E/Homeless (Spn-E), and Qin/Kumo (Qin) [64,[77][78][79].…”
Section: The Pirna Pathway In Drosophila Ovaries: the Outlinementioning
confidence: 99%